Comparação entre Simulações de Laboratório e Numérica de um Microburst - Demarco, Giuliano; Barrere, Nicasio; Acevedo, Otávio; Cabeza, Cecilia; Anabor, Vagner; Rizza, Umberto; Degrazia, Gervásio (Ciência e Natura, 2011)
.